GAMBARAN KADAR HEMOGLOBIN IBU HAMIL YANG MENGKONSUMSI TABLET Fe DAN IBU HAMIL YANG MENGKONSUMSI MULTIPLE MICRO NUTRIENT (MMN) DI PUSKESMAS BAYAT DAN PUSKESMAS NGAWEN - Nurul Laili Widodo; Siti Yulaikah; Ika Winarningrum (STIKES DUTAGAMA KLATEN, 2015)
Background: Pregnant women also need vitamins and minerals in accordance with the needs of the body to optimal fetal development takes place. In addition to the fe tablet and MMN also serves for the formation of hemoglobin levels, to prevent anemia, to improve maternal health during pregnancy, childbirth and after childbirth. Research Purposes: Hemoglobin levels of pregnant women who consume tablets that consume Fe and MMN in health centers Bayat and health centers Ngawen Research Methods: This study used quantitative descriptive, cross sectional .populasi taken is 21 third trimester pregnant women in the antenatal health centers and health centers Bayat Ngawen 30 pregnant women who consume Fe, so the total 51 maternal hamil. Teknik purposive sampling with data analysis using frequency distribution. Research Results: Respondents mostly aged 20-35 years old, high school education, occupation housewife and mother parity is largely primipara. hemoglobin levels in pregnant women who consume tablets Fe and MMN majority with hemoglobin levels 11gr% Conclusion: Hemoglobin levels in pregnant women who consume the majority of tablet Fe with hemoglobin levels 11gr%. Hemoglobin levels in pregnant women who consume the majority MMN with hemoglobin levels 11gr%.